Pharmacogenomics and treatment for dementia induced by Alzheimer''s disease. (July 2008) - Gupta, Meenal; Kaur, Harpreet; Grover, Sandeep; Kukreti, Ritushree
Pharmacogenomics is the study of interindividual genetic variability, which plays a significant role in defining drug response and toxicity. As research has graduated from studying single candidate genes to whole-genome scans, pharmacogenomics is beginning to make its impact on the therapeutics of complex CNS disorders, such as schizophrenia, Parkinson''s disease and Alzheimer''s disease. Alzheimer''s disease is a progressive complex disorder, where genetic predisposition interacts with environmental factors. With conventional therapeutics only providing symptomatic treatment, the current focus of the pharmaceutical industry is on novel strategies with an etiopathogenic orientation. In this review, we have summarized the current knowledge of pathogenetic mechanisms of Alzheimer''s disease, with a focus on the known relevant molecules and the potential of pharmacogenomics in translating this knowledge of human genome variability into efficacious and safer therapeutics.